Sustainability of Groundwater for Irrigation Purposes in Semi-arid Parts of Namibia - Amwele, Hilma Rantilla; Kgabi, Nnenesi Anna; Kandjibi, Liisa Indileni (Frontiers in Water, 2021)
Groundwater quality data from 1137 boreholes in 10 regions of Namibia were assessed for Sodium Adsorption Ratio (SAR), Kelly’s Ration (KR), Sodium Percentage (Na%), Magnesium Adsorption Ratio (MAR), Total Hardness (TH), Soluble Sodium Percentage (SSP), Potential Salinity (PS), Electrical Conductivity (EC) and Total Dissolved Solids (TDS) to determine the suitability for irrigation. The groundwater was classified as follows: SSP as fair and poor; PS as not suitable for irrigation; EC very high; TDS as slightly moderate and unsuitable for agricultural purpose; and Na% as doubtful and unsuitable. The results was due to higher concentrations for regions such as Erongo region EC, TDS, SO42-, Cl-, Ca2+ and K+; Hardap region Cl-, Ca2+ and K+; Karas region SO42-, Cl- and K+; Kavango and Khomas regions K+; Kunene Cl- and K+; Ohangwena region Mg2+ and K+; Omaheke and Otjozondjupa regions SO42-, Mg2+ and K+; Zambezi region SO42-, Cl-, Ca2+ and K+ that exceeded the FAO guideline for irrigation water quality. Other water quality criteria had inverse groundwater classification such as SAR as excellent and good water in all regions; in 70% of the regions MAR classified as recommended for irrigation; KR as groundwater safe for irrigation and TH classified groundwater as soft water.